Teaching Tamil as a Second Language to Tribal School Students by Using Communicative Language Teaching (International Journal of Food and Nutritional Sciences, 2023)
Teaching Tamil as a second language to Tribal students by using a communicative language teaching. The communicative language teaching (CLT) approach is a popular method for teaching Tamil as a second language. It can be used to teach Tamil to tribal students. It provides students real-life and work situations to help them master the language. CLT focuses on fluency and student-tailored language use. CLT encourages students to actively engage in meaningful communication through activities like role-plays, pair discussions, and group work. It allows students to use their natural strategies for language acquisition, which helps them learn to use the language.